Synthesis and antibacterial activity of cationic phthalocyanines - Pereira, Joana Brás (2012)
Antimicrobial photodynamic therapy (aPDT) was described more than 100 years ago, but its potential as an alternative to combating microorganisms, was only recognized when antibiotic resistance became an important public health issue. aPDT refers to the action of 3 non-toxic elements: a photosensitizer, light and molecular oxygen that, when combined, results in the production of singlet oxygen (1O2) and/or free radicals which are cytotoxic to target cells. The aim of this work was to synthetize, evaluate and compare the photoinactivation efficiency of new cationic phthalocyanines (Pcs) derivatives. Three new derivatives, tetra and octa-thio-pyridinium Pcs, 17, 18 and 19, were tested against Gram-negative bacteria. A recombinant bioluminescent Escherichia coli strain was used to assess, in real time, the photoinactivation efficiency of these cationic Pcs, under white and red light. After a pre-incubation period with 20 μmol L-1 of PS in the dark, the pure bacterial suspensions were irradiated with white light (400-800 nm) or red light (620- 750 nm) at a fluence rate of 150 mW cm-2, for 30 minutes. Dark and light controls were performed in all experiments. The cellular localization, uptake, 1O2, photophysical and photochemical tests such as photostability, solubility and fluorescence quantum yields were also determined, in order to evaluate the potential of these new Pcs as antibacterial agents. Pc 18 was the most effective photosensitizer, causing a 5 logs reduction in bioluminescence after 30 minutes of irradiation under white or red lights. The photoinactivation efficiency of the Pc 19 was similar (5 logs reduction in bioluminescence) to that of 18 when irradiated with white light, but the efficiency of inactivation was reduced (2.1 logs reduction in bioluminescence) under red light. Pc 17 was the least effective PS, causing only 2.1 log bioluminescence reduction under white light and 1 log decrease under red light. The three new cationic thio-pyridinium phthalocyanines with different physicochemical properties have different photoinactivation efficiencies to inactivate a gram negative bacterium. Several factors such as aggregation, 1O2 generation, number of thio-pyridinium groups, cellular uptake/localization and irradiation conditions could cause the different efficiency observed. The high photodynamic efficiency of compound 18 under red light is of special interest for clinical applications, since red light is the most preferable for treatment of microbial infections, because it penetrates deeper into infected human tissues.